Balance of Interests in the Mechanism of Protection of Industrial Property Rights - KOVAL, Iryna; DZHUMAGELDIYEVA, Gulnara; DEREVYANKO, Bogdan; VENEDIKTOVA, Iryna; PATSURIIA, Nino; PATIUK, Svitlana (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
The research deals with the relationship of private and public interests that are implemented in intellectual property relations and balance of these interests in mechanism of protection. This study uses the complex of main known methods of scientific knowledge: historical legal, forecasting, hermeneutical semantic, structural functional, logical semantic, dogmatic, complex analysis, system structural, comparative. The purpose of the study is determining the scope, content and relationship of interests in the intellectual property relations, justifying the conceptual foundations of balancing these interests in the management of intellectual capital through the legal regulation and economic mechanisms. The authors conclude that efficient functioning of intellectual property relations in terms of their scope, content and relationship of interests can be ensured only by means of legal regulation, which organically combines dispositive and imperative principles. The interdependence of such principles determines the key basis of the legal regulation of intellectual property management and should be reflected in all aspects of the development of intellectual property relations, in particular, the grounds for their emergence, change, termination, subject composition, conceptual distinguishing features of legal relations of right holders, etc.